Impact of revascularization guided by functional testing in ischaemic cardiomyopathy . (4th July 2022) - Ródenas-Alesina, Eduard; Romero-Farina, Guillermo; Jordán, Pablo; Herrador, Lorena; Espinet-Coll, Carina; Pizzi, María Nazarena; Ribera, Aida; Barrabés, José A; Aguadé-Bruix, Santiago; Ferreira-González, Ignacio
Abstract: Aims: The burden of ischaemia is a risk factor for adverse outcomes in ischaemic cardiomyopathy (ICM) but is not systematically tested when deciding on revascularization. Limited data exists in patients with ICM regarding the interaction between ischaemia and early coronary revascularization (ECR). This study sought to determine if the burden of ischaemia modifies the outcomes of ECR in ICM. Methods and results: Consecutive patients with ICM (left ventricular ejection fraction < 40%) with a stress-rest gated single-photon emission computed tomography ( N = 747) were followed-up for ECR and major cardiovascular events (MACEs, cardiovascular death, myocardial infarction, or heart failure hospitalization). A 1:1 matched population was selected using a propensity score for ECR. The interaction between ischaemia and ECR was evaluated in the matched cohort. In the initial cohort, 131 patients underwent ECR. Of them, 109 were matched to non-ECR patients. After a median follow up of 4.1 years, 102 (46.8%) patients experienced a MACE. The effect of revascularization on MACE was dependent of the percent of ischaemia ( P for the interaction at 10% ischaemia = 0.021), so that a trend towards a decreased risk of MACE was seen in patients with >10% of ischaemia [hazard ratio (HR) = 0.59 (0.30–1.18)], whereas a non-significant increase of MACE was observed in those with <10% ischaemia (HR = 1.67 [0.94–2.96]). Conclusions: In a contemporary cohort of patients with ICM, the beneficial effects of ECR may be mediated by the percent of ischaemia. This study supports stress testing in ICM and an ischaemia-guided approach for ECR. Graphical Abstract: Graphical Abstract Study design. Cumulative incidence function according the percent of ischaemia and referral for ECR.